TEACHERS' PERCEPTIONS TOWARDS THE PRACTICE OF ASSESSMENT IN ONLINE CLASSROOM DURING PANDEMIC OF COVID-19 - Agnes Lintangsasi Wicaksono; Syafi'ul Anam (ELite Journal : International Journal of Education, Language, and Literature, 2022)
This study aimed to examine the teachers’ perceptions towards online assessment due to the Covid-19 pandemic, including how the practice went, the challenges faced, and what teachers' opinions were. Four English teachers of secondary schools participated in this study. The interview sections were employed to gather data on teachers’ perceptions of the online assessment practice. Then, the data were analyzed qualitatively. Finally, this study found out that the practice of online assessment depended much on technology. The teachers exploited many online software and applications to support the assessment process. The technology was also able to assess the students formatively and summatively. Furthermore, the challenges faced by the teachers were the internet connection problem, lack of physical communication with the students, the impracticality of scoring, unmotivated students, and low integrity of students’ results. Finally, the teachers' perceptions of the online assessment were positive and negative. The teachers felt excited to try the new technology to boost the assessment process. However, many of them also preferred the offline class to assess the students.